Stroke as a Cause of Death in Death Certificates of Patients with Dementia: A Cohort Study from the Swedish Dementia Registry - Subic, Ana; Zupanic, Eva; von Euler, Mia; Norrving, Bo; Cermakova, Pavla; Religa, Dorota; Winblad, Bengt; Kramberger, Milica G; Eriksdotter, Maria; Garcia-Ptacek, Sara (Current Alzheimer research, 2018)
INTRODUCTION: Patients with dementia may be at a higher risk for death from stroke. We aimed to describe characteristics of dementia patients that died from ischemic stroke (IS) in Sweden. METHODS: A retrospective longitudinal analysis of prospectively collected data of patients registered into the Swedish Dementia Registry was conducted. Data on causes of death, drugs and comorbidities were acquired from the Swedish nationwide health registers. Deaths were attributed to stroke if the death certificate contained stroke as a cause of death and the patient had a stroke registered in Riksstroke, the Swedish Stroke Register, in the year preceding death. Demographic data at the time of dementia diagnosis was compared between patients dying from IS and registered in Riksstroke, patients dying from IS without being registered in Riksstroke and those dying from other causes. RESULTS: Out of 49823 patients diagnosed with dementia between 2007 and 2014 in primary care or specialist clinics, 14170 (28.4%) had died by the end of 2014. Of these 1180 (8.3%) had IS in their death certificate, of which 459 (38.9%) had been registered in Riksstroke. In patients who died of IS the most common type of dementia was vascular dementia while those died from other causes were most often diagnosed with Alzheimer's dementia (AD). Patients who died from IS and were registered in Riksstroke had higher MMSE score compared to other groups. Patients who died from IS took more cardiovascular medications. There were no differences in the use of antipsychotics, antidepressants, acetylcholinesterase inhibitors, memantine, anxiolytics, or hypnotics between the groups. CONCLUSIONS: There was a relatively high number of patients who died from IS as shown in their death certificate but had not been registered in Riksstroke in the year before death. This creates concerns on the accuracy of death certificate stroke diagnoses, particularly for deaths taking place outside hospitals.
Keywords: Stroke; demence; Death Certificates; ischemic stroke; Swedish dementia registry; Cohort Studies; úmrtní listy; registrace; mužské pohlaví; příčina smrti; Sweden; Registries; cévní mozková příhoda; kohortové studie; ženské pohlaví; Humans; death certificate; Dementia; Swedish Stroke Registry; Švédsko; riksstroke.; Female; SveDem; dementia; Cause of Death; lidé; Male